2017
DOI: 10.1002/jso.24720
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 8th edition American Joint Commission on Cancer (AJCC) staging system for patients with intrahepatic cholangiocarcinoma: A surveillance, epidemiology, and end results (SEER) analysis

Abstract: The new AJCC 8th-edition staging system for ICC was largely comparable to the 7th-edition version and did not provide a marked improvement in overall prognostic discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 32 publications
4
78
0
Order By: Relevance
“…Our multivariate analyses showed that, besides the maturity of FTS, tumor multiplicity, the presence of MVI, and LN metastasis were independent risk factors for survival, which were in accordance with previously established staging systems . It should be noted that tumor size failed to stratify survival in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our multivariate analyses showed that, besides the maturity of FTS, tumor multiplicity, the presence of MVI, and LN metastasis were independent risk factors for survival, which were in accordance with previously established staging systems . It should be noted that tumor size failed to stratify survival in this study.…”
Section: Discussionsupporting
confidence: 90%
“…were in accordance with previously established staging systems [19,20]. It should be noted that tumor size failed to stratify survival in this study.…”
Section: © Alphamed Press 2018supporting
confidence: 88%
See 1 more Smart Citation
“…Accurate assessment of tumor stages following surgical resection is important for predicting patient prognoses and providing adequate information to guide adjuvant treatment. To date, two high‐volume studies have aimed to validate the prognostic impact of the 8th edition of the AJCC staging system for ICC – an international study that included 14 major hepatobiliary centers and a study conducted in the USA based on the surveillance epidemiology and end result (SEER) database . These studies suggested that the prognostic power of the criteria in the 8th edition of the AJCC staging system was either partially improved or comparable with that of the 7th edition.…”
Section: Discussionmentioning
confidence: 99%
“…While these staging systems perform adequately, some investigators have suggested that the prognostic performance of AJCC/UICC and LCSGJ need further improvements. 10,26 While several groups have suggested refinements, no current staging schema has incorporated tumor biomarkers. The current study was important because we explicitly focused on defining the impact of CA 19-9 and CEA levels on long-term prognosis following resection of ICC.…”
Section: Discussionmentioning
confidence: 99%